Double-doped P2 / O3 phase high-performance sodium-ion battery layered oxide positive electrode material, preparation method and application of double-doped P2 / O3 phase high-performance sodium-ion battery layered oxide positive electrode material

By using a two-position doping strategy and a multi-process combination method in the positive electrode material of sodium ion battery, the P2/O3 phase hybrid structure was constructed, which solved the problem of insufficient cycle stability and reversible specific capacity of existing materials, and achieved efficient Na+ The transmission and stable crystal structure significantly improves battery performance.

CN119208587APending Publication Date: 2024-12-27WUHAN UNIV

Patent Information

Application Number
CN202411220514.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

There are insufficient cyclic stability and reversible specific capacity of existing sodium ion battery positive electrode materials, which is difficult to meet the requirements of high-efficiency Na+ transmission rate and stable crystal structure.

Method used

Using the double-position doping strategy, doping at the Na and TM positions simultaneously to build a hybrid P2/O3 phase structure, combining sol-gel method, solid-phase sintering and ball milling method to prepare layered oxide positive electrode materials to enhance structural stability and Na+ diffusion kinetics.

Benefits of technology

It significantly improves the stability and rate performance of layered oxides, achieves high reversible specific capacity and excellent cycling performance, and is suitable for sodium ion battery positive electrode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208587A_ABST
    Figure CN119208587A_ABST
Patent Text Reader

Abstract

The invention discloses a double-doped P2 / O3 phase high-performance sodium ion battery layered oxide positive electrode material as well as a preparation method and application thereof, and belongs to the technical field of sodium ion batteries. The chemical general formula of the P2 / O3 phase layered oxide is NaaM1bM2cNidFeeMnfXgO2, 0.5 < = a < 1.1, 0 < = b < = 0.2, 0 < = c < = 0.2, 0.1 < = d < = 0.5, 0.1 < = e < = 0.6, 0.1 < = f < = 0.6, 0 < g < = 0.2, d + e + f + g = 1, b and c are not 0 at the same time, and values of a, b, c, d, e, f and g enable the general formula to meet valence equilibrium; m1 and M2 are doped at the Na position, and X is doped at the TM position. According to the invention, a double-position co-doping strategy is adopted to prepare the double-position doped P2 / O3 phase layered oxide, when the double-position doped P2 / O3 phase layered oxide is used as the positive electrode material of the sodium ion battery, the reversible discharge capacity under 0.1 c reaches up to 140 mAh.g <-1 >, and the double-position doped P2 / O3 phase layered oxide has excellent cycle performance and excellent rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a dual-site doped P2 / O3 phase high-performance sodium ion battery layered oxide positive electrode material, a preparation method and an application thereof. Background Art

[0002] The depletion of fossil fuels and the escalation of environmental pollution have prompted the rapid development of clean energy, including wind energy, solar energy, tidal energy, etc. Among modern energy storage technologies, electrochemical energy storage is the most widely used and promising energy storage technology. Lithium-ion batteries are widely used due to their high capacity, extended cycle life, and stable energy storage capacity. However, the growing market demand for lithium and the continuous reduction of lithium resources in nature have led to large fluctuations in the price of lithium-ion batteries. Therefore, it is necessary to explore alternative or supplementary energy storage batteries. Sodium-ion batteries have similar working principles and electrochemical performance characteristics to lithium-ion batteries, and sodium resources are abundant and widely distributed, avoiding the challenges of limited lithium / cobalt resources and environmental pollution. Therefore, sodium-ion batteries have received increasing attention. Since the sodium storage performance and production cost are dominated by the cathode performance, the development of cathode materials with large-scale production capacity is the key to the commercial application of sodium-ion batteries. The positive electrode materials of sodium ion batteries mainly include: layered oxides, polyanion compounds, and Prussian blue analogues. Among them, layered oxide positive electrode materials are one of the positive electrode materials with the most promising commercial applications due to their advantages such as suitable operating voltage, high reversible capacity and easy synthesis.

[0003] Layered oxide cathode materials (Na x TMO2) is mainly divided into P2 type and O3 type, the letters 'P' and 'O' represent triangular prism and octahedron respectively; the numbers '2' and '3' refer to the number of oxygen accumulation layers in a unit cell. O3 phase positive electrode materials have sufficient Na content (x ~ 0.9-1.0) and have high reversible specific capacity, but poor cycle stability; P2 type materials have insufficient sodium content (x ~ 0.6-0.8) and generally low capacity, but show good cycle stability and high Na + Single-phase materials cannot solve the inherent problems of O3 and P2 phases, while the unique hybrid structure of P2 / O3 phase contributes to the high efficiency of Na+ in the sodium ion cathode. + The P2 / O3 hybrid phase material utilizes the enhanced Na + The transmission efficiency, as well as the rich sodium ion content of the O3 phase and the reversible structural phase change characteristics, can construct a sodium ion battery positive electrode material with excellent cycle performance, high reversible specific capacity and excellent rate performance. Summary of the invention

[0004] In view of the deficiencies of the above-mentioned prior art, the present invention provides a dual-site doped P2 / O3 phase high-performance sodium ion battery layered oxide positive electrode material, a preparation method and its application. The present invention utilizes a dual-site doping strategy to construct a dual-phase hybrid structure, and the prepared layered oxide positive electrode material has a high specific capacity, excellent cycle stability and outstanding rate performance.

[0005] To achieve the above purpose, the specific technical solutions of the present invention are as follows:

[0006] In the first aspect, the present invention provides a dual-site doped P2 / O3 phase layered oxide having a chemical formula of Na a M 1b M 2c Ni d Fe e Mn f X g O2, wherein 0.5≤a<1.1, 0≤b≤0.2, 0≤c≤0.2, 0.1≤d≤0.5, 0.1≤e≤0.6, 0.1≤f≤0.6, 0<g≤0.2, and d+e+f+g=1, b and c are not 0 at the same time, and the values ​​of a, b, c, d, e, f, and g make the corresponding general formula satisfy the valence balance; the M1 and M2 are doped at the Na position, and the X is doped at the TM position.

[0007] The layered oxide in the present invention is a P2 / O3 dual-phase structure. Both the P2 phase and the O3 phase are typical layered oxides, each with its own advantages and challenges. However, the O3 phase material has sufficient Na content (x ~ 0.9-1.0) and has a high reversible specific capacity, but poor cycle stability. The P2-type material has insufficient sodium content (x ~ 0.6-0.8) and generally has a low capacity, but exhibits high Na due to its low energy barrier. + Single-phase materials cannot solve the inherent problems of O3 and P2 phases, while the unique hybrid structure of P2 / O3 phase helps to show efficient Na + The P2 / O3 hybrid phase material utilizes the enhanced Na + The transmission efficiency, as well as the rich sodium ion content of the O3 phase and the reversible structural phase change characteristics, can construct a sodium ion battery positive electrode material with excellent cycle performance, high reversible specific capacity and excellent rate performance.

[0008] The present invention adopts a method of co-doping at the Na position and the TM position. The conventional P2 / O3 phase layered oxide is doped only at the TM position. When the Na content is changed, its phase structure is changed. The dual-position doping strategy of the present invention can, on the one hand, introduce transition metal ions into the TM layer to suppress the unfavorable multiphase transition; on the other hand, reasonable Na position substitution can enhance the structural stability and Na + Diffusion kinetics are also important. In this case, the optimal dual-site substitution that combines the advantages of both Na layer and TM layer substitution may achieve excellent electrochemical performance. Experimental results show that the synergistic effect of multi-site doping and multi-element doping can indeed significantly improve the stability and rate performance of layered oxides.

[0009] Preferably, both M1 and M2 are selected from one or more alkali metal elements or alkaline earth metal elements, and M1 and M2 are different elements.

[0010] Preferably, X is selected from one or more of the elements Zn, Al, Co, Cu, Mg, B, V, Sn, Cr, and Ti.

[0011] Preferably, the dual-site doped P2 / O3 phase layered oxide is prepared by adopting a multi-site doping strategy at the Na site and the TM site.

[0012] Preferably, the dual-site doped P2 / O3 phase layered oxide is prepared by sol-gel method, solid phase sintering and ball milling method.

[0013] In a second aspect, the present invention provides a method for preparing the dual-site doped P2 / O3 phase layered oxide, comprising the following steps:

[0014] S1. Dissolve a sodium source, an M1 source, an M2 source, a nickel source, an iron source, a manganese source, and an X source in a solvent according to the molar ratio of each element in the chemical formula to obtain a mixed solution;

[0015] S2, stirring the mixed solution at a speed of 400-600 r / min for 30-60 min, adding the chelating agent, continuing stirring for 30-60 min, and adjusting the pH with ammonia water until the solution is neutral;

[0016] S3, heating the solution to 80-120 °C and keeping it warm for 4-8 h until a wet gel is obtained;

[0017] S4, drying the wet gel at 100-120 °C for 18-24 h until a dry gel is obtained;

[0018] S5. Grind the dry gel into powder, pre-sinter it at 400-500 °C in air atmosphere for 2-5 h, and then calcine it at 800-1000 °C in air atmosphere for 8-16 h to obtain a dual-site doped P2 / O3 phase layered oxide.

[0019] The present invention prepares P2 / O3 phase layered oxide by integrating sol-gel method, solid phase sintering method and ball milling method. The preparation method is simple, low-cost, environmentally friendly and non-toxic, and the obtained layered oxide has the advantages of uniform element mixing, good particle size dispersion, good morphology uniformity, etc.

[0020] Preferably, the sodium source includes at least one of sodium carbonate, sodium acetate, sodium nitrate, and sodium bicarbonate; the M1 source includes at least one of carbonate M1, acetic acid M1, sulfuric acid M1, oxalic acid M1, and nitric acid M1; the M2 source includes at least one of carbonate M2, acetic acid M2, sulfuric acid M2, oxalic acid M2, and nitric acid M2; the nickel source includes at least one of nickel carbonate, nickel acetate, nickel nitrate, and nickel sulfate; the iron source includes at least one of ferrous acetate, ferrous acetate, ferrous sulfate, ferric nitrate, and ferrous oxalate; the manganese source includes at least one of manganese nitrate, manganese acetate, manganese sulfate, manganese oxalate, and manganese carbonate; the X source includes at least one of carbonate X, acetic acid X, sulfuric acid X, oxalic acid X, and nitric acid X.

[0021] Preferably, the solvent is deionized water, which can dissolve all raw materials.

[0022] Preferably, the chelating agent is citric acid monohydrate or citric acid trihydrate, and after the chelating agent is added, stirring needs to be continued at a speed of 400-600 r / min for 30-60 min.

[0023] Preferably, the volume ratio of the solvent to the chelating agent is 1:1.

[0024] Preferably, the calcination temperature is 850-950°C, and the heating rate is 3-10°C / min.

[0025] In a third aspect, the present invention provides the use of the dual-site doped P2 / O3 phase layered oxide in the preparation of positive electrode materials for sodium ion batteries.

[0026] Compared with the prior art, the present invention is beneficial in that:

[0027] 1. The present invention adopts a dual-site doping strategy to dual-site co-doping at the Na site and the TM site, doping alkali metal elements or alkaline earth metal elements at the Na site and doping transition metal elements at the TM site. The original P2-type layered oxide can be transformed into a P2 / O3 hybrid structure without changing the Na content, and a dual-site doped P2 / O3 phase layered oxide can be prepared as a positive electrode material for a sodium ion battery, and its electrochemical performance is significantly improved.

[0028] 2. The present invention combines the sol-gel method, the high-temperature sintering method and the ball milling method to prepare a P2 / O3 phase layered oxide material with uniform element mixing; SEM, TEM and XRD experimental results show that the material prepared by the present invention has good particle size dispersion, good morphology uniformity, and a P2 / O3 dual-phase structure. Using it as a positive electrode material for a sodium ion battery can greatly improve the cycle performance and reversible capacity of the positive electrode material of the sodium ion battery.

[0029] 3. When the layered oxide in the present invention is used as the positive electrode material of sodium ion battery, the electrochemical performance is relatively superior, and the reversible discharge capacity at 0.1c is as high as 140 mAh·g -1 , with excellent cycle performance (80% capacity retention after 250 cycles at 1c), and excellent rate performance (96 mAh g at 5c and 10c, respectively). -1 、82 mAh·g -1 reversible discharge capacity). BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a SEM image of the positive electrode material prepared in Example 1;

[0031] Figure 2 HR~TEM image of the positive electrode material prepared in Example 1;

[0032] Figure 3 XRD pattern of the positive electrode material prepared in Example 1;

[0033] Figure 4 The first cycle discharge diagram of the positive electrode material prepared in Example 1 at 1c, 5c, and 10c rates;

[0034] Figure 5 This is a cycle performance diagram of the positive electrode material prepared in Example 1 at a rate of 1c;

[0035] Figure 6 This is a cycle performance diagram of the positive electrode material prepared in Example 1 at a rate of 10c;

[0036] Figure 7 This is a rate performance diagram of the positive electrode material prepared in Example 1. DETAILED DESCRIPTION

[0037] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] The present invention provides a dual-site doped P2 / O3 phase layered oxide, the chemical formula of which is Na a M 1b M 2c Ni d Fe e Mn f X g O2, wherein 0.5≤a<1.1, 0≤b≤0.2, 0≤c≤0.2, 0.1≤d≤0.5, 0.1≤e≤0.6, 0.1≤f≤0.6, 0<g≤0.2, and d+e+f+g=1, b and c are not 0 at the same time, and the values ​​of a, b, c, d, e, f, and g make the corresponding general formula satisfy the valence balance; the M1 and M2 are doped at the Na position, and the X is doped at the TM position.

[0039] In some examples, both M1 and M2 are selected from one or more of alkali metal elements or alkaline earth metal elements, and M1 and M2 are different elements.

[0040] In some examples, X is selected from one or more of the elements Zn, Al, Co, Cu, Mg, B, V, Sn, Cr, and Ti.

[0041] The preparation method of the dual-site doped P2 / O3 phase layered oxide comprises the following steps:

[0042] S1. Dissolve a sodium source, an M1 source, an M2 source, a nickel source, an iron source, a manganese source, and an X source in a solvent according to the molar ratio of each element in the chemical formula to obtain a mixed solution;

[0043] S2, stirring the mixed solution at a speed of 400-600 r / min for 30-60 min, adding the chelating agent, continuing stirring for 30-60 min, and adjusting the pH with ammonia water until the solution is neutral;

[0044] S3, heating the solution to 80-120 °C and keeping it warm for 4-8 h until a wet gel is obtained;

[0045] S4, drying the wet gel at 100-120 °C for 18-24 h until a dry gel is obtained;

[0046] S5. Grind the dry gel into powder, pre-sinter it at 400-500 °C in air atmosphere for 2-5 h, and then calcine it at 800-1000 °C in air atmosphere for 8-16 h to obtain a dual-site doped P2 / O3 phase layered oxide.

[0047] In some examples, the sodium source includes at least one of sodium carbonate, sodium acetate, sodium nitrate, and sodium bicarbonate; the M1 source includes at least one of carbonate M1, acetic acid M1, sulfuric acid M1, oxalic acid M1, and nitric acid M1; the M2 source includes at least one of carbonate M2, acetic acid M2, sulfuric acid M2, oxalic acid M2, and nitric acid M2; the nickel source includes at least one of nickel carbonate, nickel acetate, nickel nitrate, and nickel sulfate; the iron source includes at least one of ferrous acetate, ferrous acetate, ferrous sulfate, ferric nitrate, and ferrous oxalate; the manganese source includes at least one of manganese nitrate, manganese acetate, manganese sulfate, manganese oxalate, and manganese carbonate; the X source includes at least one of carbonate X, acetic acid X, sulfuric acid X, oxalic acid X, and nitric acid X.

[0048] In some examples, the chelating agent is citric acid monohydrate or citric acid trihydrate, and after the chelating agent is added, stirring needs to be continued at a speed of 400-600 r / min for 30-60 min.

[0049] In the following specific examples, the chelating agent is citric acid monohydrate; the solvent is deionized water, and the amounts of the citric acid monohydrate and the deionized water are both 100 mL.

[0050] Example 1

[0051] A dual-site doped P2 / O3 phase high-performance sodium ion battery layered oxide positive electrode material, the preparation steps are as follows:

[0052] According to the chemical formula Na a M 1b M 2c Ni d Fe e Mn f X gThe molar ratio of each metal element in O2 (wherein, M1 and M2 are each selected from one element; a is 0.8; b is 0.05; c is 0.05; d is 0.2; e is 0.2; f is 0.55; g is 0.05) is adjusted, sodium acetate, M1 acetate, M2 acetate (M1 is Ca, M2 is K), nickel acetate, ferric nitrate, manganese acetate, and X acetate (X is Mg) are dissolved in a solvent to obtain a mixed solution; the mixed solution is placed on a stirring table and stirred at a speed of 500 r / min for 45 min, a chelating agent is added to the mixed solution, stirring is continued for 30 min, and ammonia water is used to adjust the pH of the solution to neutral; the solution is placed in an oil bath pot and heated at 100°C for 5 h until a wet gel is obtained; the wet gel is placed in a drying oven and dried at 120°C for 20 h until a dry gel is obtained; the dry gel is ground into powder in an agate mortar, placed in a crucible, placed in a muffle furnace, and heated at 500 The samples were pre-sintered at 100 ℃ in air atmosphere for 6 h and then calcined at 900 ℃ in air atmosphere for 12 h to obtain a dual-site doped P2 / O3 phase high-performance sodium ion battery layered oxide cathode material.

[0053] Figure 1 This is a SEM image of the dual-site doped P2 / O3 phase high-performance sodium ion battery layered oxide positive electrode material prepared in Example 1. It can be seen from the figure that the material exhibits the basic morphology of layered oxide and has good particle size dispersion.

[0054] Figure 2 This is the HR~TEM image of the dual-site doped P2 / O3 phase high-performance sodium ion battery layered oxide positive electrode material prepared in Example 1. It can be seen from the figure that the material has a P2 / O3 dual-phase structure.

[0055] Figure 3 This is the XRD pattern of the dual-site doped P2 / O3 phase high-performance sodium ion battery layered oxide positive electrode material prepared in Example 1. It can be seen from the figure that the diffraction peaks of the material are sharp, indicating good crystallinity. All peaks correspond well to the standard card peaks of P2~ (PDF#54-0894) and O3~ (PDF#53-0349), and there are no extra impurity peaks.

[0056] Example 2

[0057] A dual-site doped P2 / O3 phase high-performance sodium ion battery layered oxide positive electrode material, the preparation steps are as follows:

[0058] According to the chemical formula Na a M 1b M 2c Ni d Fe e Mn f X gThe molar ratio of each metal element in O2 (M1 is one element, c is 0; a is 0.8; b is 0.05; d is 0.2; e is 0.2; f is 0.55; g is 0.05) is adjusted, sodium acetate, acetate M1 (M1 is Ca), nickel acetate, ferric nitrate, manganese acetate, and acetate X (X is Mg) are dissolved in a solvent to obtain a mixed solution; the mixed solution is placed on a stirring table and stirred at a speed of 500 r / min for 45 min, and then a chelating agent is added to the mixed solution. After continuing to stir for 30 min, the pH of the solution is adjusted to neutral with ammonia water; the solution is placed in an oil bath pot and heated at 100 °C for 5 h until a wet gel is obtained; the wet gel is placed in a drying oven and dried at 120 °C for 20 h until a dry gel is obtained; the dry gel is ground into powder in an agate mortar, placed in a crucible, placed in a muffle furnace, pre-sintered at 500 °C in an air atmosphere for 6 h, and then heated at 900 ℃ and calcined in air atmosphere for 12 h to obtain a dual-site doped P2 / O3 phase high-performance sodium ion battery layered oxide positive electrode material.

[0059] Example 3

[0060] A dual-site doped P2 / O3 phase high-performance sodium ion battery layered oxide positive electrode material, the preparation steps are as follows:

[0061] According to the chemical formula Na a M 1b M 2c Ni d Fe e Mn f X g The molar ratio of each metal element in O2 (b is 0, M2 is K; a is 0.8; c is 0.1; d is 0.2; e is 0.2; f is 0.55; g is 0.05) is adjusted, sodium acetate, M2 acetate (M2 is K), nickel acetate, ferric nitrate, manganese acetate, and X acetate (X is Mg) are dissolved in a solvent to obtain a mixed solution; the mixed solution is placed on a stirring table and stirred at a speed of 500r / min for 45 min, and then a chelating agent is added to the mixed solution. After continuing to stir for 30 min, the pH of the solution is adjusted to neutral with ammonia water; the solution is placed in an oil bath pot and heated at 100°C for 5 h until a wet gel is obtained; the wet gel is placed in a drying oven and dried at 120°C for 20 h until a dry gel is obtained; the dry gel is ground into powder in an agate mortar, placed in a crucible, placed in a muffle furnace, pre-sintered at 500°C in an air atmosphere for 6 h, and then heated at 900 ℃ and calcined in air atmosphere for 12 h to obtain a dual-site doped P2 / O3 phase high-performance sodium ion battery layered oxide positive electrode material.

[0062] Comparative Example 1

[0063] A P2 phase sodium ion battery layered oxide positive electrode material doped only at the TM position, the preparation steps are as follows:

[0064] According to the chemical formula Na a M 1b M 2c Ni d Fe e Mn f X g The molar ratio of each metal element in O2 (b and c are 0; a is 0.8; d is 0.2; e is 0.2; f is 0.55; g is 0.05) is determined, and sodium acetate, nickel acetate, ferric nitrate, manganese acetate, and acetate X (X is Mg) are dissolved in a solvent to obtain a mixed solution; the mixed solution is placed on a stirring table and stirred at a speed of 500 r / min for 45 min, and then a chelating agent is added to the mixed solution, and after continuing to stir for 30 min, the pH of the solution is adjusted to neutral with ammonia water; the solution is placed in an oil bath pot and heated at 100 °C for 5 h until a wet gel is obtained; the wet gel is placed in a drying oven and dried at 120 °C for 20 h until a dry gel is obtained; the dry gel is ground into powder in an agate mortar, placed in a crucible, placed in a muffle furnace, pre-sintered at 500 °C in an air atmosphere for 6 h, and then calcined at 900 °C in an air atmosphere for 12 h, obtaining a P2 phase sodium ion battery layered oxide positive electrode material doped only at the TM site.

[0065] Comparative Example 2

[0066] An undoped P2 phase sodium ion battery layered oxide positive electrode material, the preparation steps are as follows:

[0067] According to the chemical formula Na a M 1b M 2c Ni d Fe e Mn f X gThe molar ratio of each metal element in O2 (b, c and g are 0; a is 0.8; d is 0.2; e is 0.2; f is 0.6) is calculated, sodium acetate, nickel acetate, ferric nitrate and manganese acetate are dissolved in a solvent to obtain a mixed solution; the mixed solution is placed on a stirring table, stirred at a speed of 500 r / min for 45 min, a chelating agent is added to the mixed solution, and stirring is continued for 30 min, and then the pH of the solution is adjusted to neutral with ammonia water; the solution is placed in an oil bath pot and heated at 100 ° C for 5 h until a wet gel is obtained; the wet gel is placed in a drying oven and dried at 120 ° C for 20 h until a dry gel is obtained; the dry gel is ground into powder in an agate mortar, placed in a crucible, placed in a muffle furnace, pre-sintered at 500 ° C in an air atmosphere for 6 h, and then calcined at 900 ° C in an air atmosphere for 12 h to obtain an undoped P2 phase sodium ion battery layered oxide positive electrode material.

[0068] Application Examples

[0069] The materials prepared in Examples 1 to 3 and Comparative Examples 1 to 2, the conductive agent (acetylene black) and the binder (polyvinylidene fluoride) were mixed in a mass ratio of 7:2:1, and then an appropriate amount of N-methylpyrrolidone was added. After ultrasonic dispersion, a slurry was formed. After ball milling for a certain period of time, the uniform slurry was coated on an aluminum foil and placed in a vacuum drying oven at 120 ° C for 12 h. The dried aluminum foil was compacted in a roller press and then pressed into a circular electrode sheet with a diameter of 12 mm. The prepared electrode sheet was dried in a vacuum drying oven at 60 ° C for 1 h. The dried electrode sheet was used as the positive electrode, the sodium sheet was used as the negative electrode, the glass fiber was used as the diaphragm, and the NaClO4 was used as the electrolyte to assemble a button battery (CR2032), and the electrochemical performance was tested using a blue battery system. The electrochemical properties of the materials in Examples 1 to 3 and Comparative Examples 1 to 2 at a rate of 1c are shown in Table 1.

[0070] Table 1: Electrochemical performance of cathode materials at 1c rate

[0071]

[0072] It can be seen from the data in Table 1 that the initial capacity and cycle performance of the positive electrode material prepared by the present invention are relatively superior, and the performance improvement is very obvious compared with the P2 phase layered oxide positive electrode material doped only at the TM position, the undoped P2 phase layered oxide and similar materials. Therefore, the present invention adopts a multi-site doping strategy to prepare the P2 / O3 phase layered oxide doped at the Na position and the TM position, combining the advantages of the two phases, and due to its unique hybrid structure, it helps the sodium ion battery positive electrode material to show efficient Na + The transmission rate and stable crystal structure make the initial capacity, cycle performance and rate performance show excellent performance when used as the positive electrode material of sodium ion batteries.

[0073] The first cycle charge and discharge capacities of the positive electrode material of Example 1 at 1c, 5c, and 10c rates are as follows: Figure 4 As shown in the figure, it can be seen that at 1c, 5c, and 10c rates, the first cycle discharge capacity of the positive electrode material is 100 mAh g -1 、96 mAh·g -1 、82 mAh·g -1 , the first cycle discharge can still reach a higher discharge capacity at a high rate.

[0074] The positive electrode material of Example 1 was cycled at a rate of 1c. Figure 5 As shown in the figure, it can be seen that the material can maintain a capacity of more than 80% after 250 cycles at a rate of 1c, which is higher than that of similar positive electrode materials and significantly higher than that of P2-phase layered oxide positive electrode materials that are not doped at double sites. Figure 6 As shown in the figure, the material can retain more than 80% of its capacity after 600 cycles at a high rate of 10c, indicating that the material's cycle performance is relatively stable.

[0075] The rate performance of the positive electrode material of Example 1 is as follows Figure 7 As shown in the figure, it can be seen that at a rate of 0.1c, the first cycle discharge capacity of the material can reach up to 140 mAh g -1 After being discharged at different rates, the capacity is not lost after returning to a low rate, indicating that the positive electrode material of the present invention has excellent rate performance.

[0076] In summary, the present invention adopts a dual-site doping strategy to prepare a dual-site doped P2 / O3 phase high-performance layered oxide, which, when used as a positive electrode material for a sodium ion battery, has a high initial capacity and has excellent cycle performance and outstanding rate performance.

[0077] The above specific embodiments describe the implementation of the present invention in detail, but the present invention is not limited to the specific details in the above embodiments. Within the scope of the claims and technical concept of the present invention, the technical solution of the present invention can be modified and changed in many simple ways, and these simple modifications all belong to the protection scope of the present invention.

Claims

1. A dual-site doped P2 / O3 phase layered oxide, characterized in that: The chemical formula is Na a M 1b M 2c Ni d Fe e Mn f X g O2, wherein 0.5≤a<1.1, 0≤b≤0.2, 0≤c≤0.2, 0.1≤d≤0.5, 0.1≤e≤0.6, 0.1≤f≤0.6, 0<g≤0.2, and d+e+f+g=1, b and c are not 0 at the same time, and the values ​​of a, b, c, d, e, f, and g make the corresponding general formula satisfy the valence balance; the M1 and M2 are doped at the Na position, and the X is doped at the TM position.

2. A dual-site doped P2 / O3 phase layered oxide according to claim 1, characterized in that: The M1 and M2 are both selected from one or more of alkali metal elements or alkaline earth metal elements, and the M1 and M2 are different elements.

3. A dual-site doped P2 / O3 phase layered oxide according to claim 1, characterized in that: The X is selected from one or more of the elements Zn, Al, Co, Cu, Mg, B, V, Sn, Cr, and Ti.

4. The method for preparing a dual-site doped P2 / O3 phase layered oxide according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Dissolve a sodium source, an M1 source, an M2 source, a nickel source, an iron source, a manganese source, and an X source in a solvent according to the molar ratio of each element in the chemical formula to obtain a mixed solution; S2, stirring the mixed solution at a speed of 400-600 r / min for 30-60 min, adding a chelating agent, continuing to stir for 30-60 min, and adjusting the pH of the solution to neutral; S3, heating the solution to 80-120 °C and keeping it warm for 4-8 h to obtain a wet gel; S4, drying the wet gel at 100-120°C to obtain a dry gel; S5. Grind the dry gel into powder, pre-sinter it at 400-500°C, and then calcine it at 800-1000°C to obtain a dual-site doped P2 / O3 phase layered oxide.

5. The method for preparing a dual-site doped P2 / O3 phase layered oxide according to claim 4, characterized in that: The sodium source includes at least one of sodium carbonate, sodium acetate, sodium nitrate, and sodium bicarbonate; the M1 source includes at least one of carbonate M1, acetic acid M1, sulfuric acid M1, oxalic acid M1, and nitric acid M1; the M2 source includes at least one of carbonate M2, acetic acid M2, sulfuric acid M2, oxalic acid M2, and nitric acid M2; the nickel source includes at least one of nickel carbonate, nickel acetate, nickel nitrate, and nickel sulfate; the iron source includes at least one of ferrous acetate, ferrous acetate, ferrous sulfate, ferric nitrate, and ferrous oxalate; the manganese source includes at least one of manganese nitrate, manganese acetate, manganese sulfate, manganese oxalate, and manganese carbonate; the X source includes at least one of carbonate X, acetic acid X, sulfuric acid X, oxalic acid X, and nitric acid X.

6. The method for preparing a dual-site doped P2 / O3 phase layered oxide according to claim 4, characterized in that: The chelating agent is citric acid monohydrate or citric acid trihydrate. After adding the chelating agent, stirring needs to be continued at a speed of 400-600 r / min for 30-60 min.

7. The method for preparing a dual-site doped P2 / O3 phase layered oxide according to claim 4, characterized in that: The reagent for adjusting pH is ammonia water.

8. The method for preparing a dual-site doped P2 / O3 phase layered oxide according to claim 4, characterized in that The calcination temperature is 850-950°C, and the heating rate is 3-10°C / min.

9. The method for preparing a dual-site doped P2 / O3 phase layered oxide according to claim 4, characterized in that The pre-sintering and calcining processes are both carried out in an air atmosphere.

10. Use of a dual-site doped P2 / O3 phase layered oxide as claimed in any one of claims 1 to 3 in a positive electrode material for a sodium ion battery.

Citation Information

Patent Citations

  • Positive electrode active material, preparation method thereof and sodium ion battery

    CN111554919A

  • P2 type layered metal oxide sodium ion battery positive electrode material and preparation method thereof

    CN115394988A

  • Multi-metal co-regulated layered oxide sodium-ion battery positive electrode material as well as preparation method and application thereof

    CN115939369A

  • Three-phase symbiotic layered oxide electrode material, preparation method thereof and application of three-phase symbiotic layered oxide electrode material in sodium-ion battery

    CN116143194A

  • Double-doping-site doped P2 type layered oxide composite material as well as preparation method and application thereof

    CN116845229A

Cited By

  • O3-P2 layered double-phase sodium ion battery positive electrode material and preparation method thereof

    CN120784353A